Uniqueness of algebraic unitizations of generalized pseudo effect algebras. (18th August 2019) - Yang, Aili
Abstract: We study the uniqueness of the algebraic unitizations of a generalized pseudo effect algebra (GPEA). We prove that for a weakly commutative GPEA, if its unitization is a weakly PEA, then it is unique in the sense of PEA-isomorphism.